Macbeth - Shakespeare, William, 1564-1616; Edited by Gill, Roma (Oxford, New York Oxford University Press, 2004)
Macbeth is one of the most popular texts for study by secondary students the world over. This edition includes illustrations, preliminary notes, reading lists (including websites) and classroom notes
Include Illustration
Keywords: Macbeth, King of Scotland, active 11th century -- Scotland -- Measure for measure (Shakespeare, William)